Integrating Artificial Intelligence in Diagnostic Radiology: Opportunities and Challenges for Modern Medicine - Fahad Dauwas Eid Alshammari; Azzam Fahad Al Amer; Afnan Issa Abdullah Almalahi; Arif Mishal Taisan Alshammari; Alaa Sharef Mohammad Alhmshe; Obaid Mousa Almarri; Maitha Shubrum Alshammari; Awatif Radhy J Alshammari (International Journal of Medical Toxicology and Legal Medicine, 2024)
The idea of using AI to identify diseases is looking better and better as the world’s population grows. Artificial intelligence is a new medical tool that can change how diagnoses are made and make medical care better. This is because more people means more work for radiologists. A diagnostic approach like this could make the job of a radiologist easier and get rid of the chance of differences in practice, since radiologists have different skills when it comes to recognizing and interpreting image features. New research shows that AI can be useful in radiology because it can help with image analysis, finding important things in images, making images better, setting priorities, making clinical suggestions, and creating automated protocols. Because science is changing so quickly these days, medical diagnostic methods are also changing quickly. This means that we need to think about and analyze new diagnostic methods like artificial intelligence. In our review, we will look at how well artificial intelligence and radiological picture interpretation can be used for diagnosis, as well as the pros and cons of its use and how it might grow in the future.